Occurrence and human exposure to brominated and organophosphorus flame retardants via indoor dust in a Brazilian city - Cristale, Joyce [UNESP]; Aragão Belé, Tiago Gomes [UNESP]; Lacorte, Silvia; Rodrigues de Marchi, Mary Rosa [UNESP] (Elsevier, 2018)
Indoor dust is considered an important human exposure route to flame retardants (FRs), which has arised concern due the toxic properties of some of these substances. In this study, ten organophosphorus flame retardants (OPFRs), eight polybrominated diphenyl ethers (PBDEs) and four new brominated flame retardants (NBFRs) were determined in indoor dust from different places in Araraquara-SP (Brazil). The sampled places included houses, apartments, offices, primary schools and cars. The analysis of the sample extracts was performed by gas chromatography coupled to mass spectrometry and two ionization techniques were used (electron ionization – EI; electron capture negative ionization – ECNI). OPFRs were the most abundant compounds and tris(2-butoxyethyl) phosphate (TBOEP), tris(phenyl) phosphate (TPHP), tris(1,3-dichloroisopropyl) phosphate (TDCIPP) and tris(2-chloroisopropyl) phosphate (TCIPP) were present at the highest concentrations. Among the brominated FRs, the most ubiquitous compounds were BDE-209, bis(2-ethylhexyl) tetrabromophthalate (BEH-TEBP) and decabromodiphenyl ethane (DBDPE). Statistical analysis revealed that there were differences among dust typologies for TBOEP, TDCIPP, ethylhexyl diphenyl phosphate (EHDPHP), BDE-209, 2-ethylhexyl 2,3,4,5-tetrabromobenzoate (EH-TBB), BEH-TEBP and DBDPE, which were attributed to different construction materials in each particular environment and to the age of the buildings. The highest levels of brominated FRs were observed in offices, TBOEP was at high concentration in primary schools, and TDCIPP was at high concentration in cars. A preliminary risk assessment revealed that toddlers were exposed to TBOEP levels higher than the reference dose when considering the worst case scenario. The results obtained in this study showed for the first time that although Brazil does not regulate the use of FRs, these substances are present in indoor dust at levels similar to the observed in countries that have strict fire safety standards, and that humans are exposed to complex mixtures of these contaminants via indoor dust. PBDEs, NBFRs and OPFRs were detected in indoor dust from houses, apartments, schools, offices and cars, and a risk associated to TBOEP exposure was estimated for toddlers.